A Human Right to Science?: Precarious Labor and Basic Rights in Science and Bioprospecting. Issue 1 (2nd January 2017) - Neimark, Benjamin D.; Vermeylen, Saskia
Abstract : Does everyone have the right to benefit from science? If so, what shape should benefits take? This article exposes the inequalities involved in bioprospecting through a relatively neglected human right, the right to benefit from science (HRS). Although underexplored in the literature, it is acknowledged that market-based conservation practices, such as bioprospecting, often rely on cheap "casual" labor. In contrast to critical discourses exposing the exploitation and misappropriation of indigenous people's cultural and self-determination rights in relation to bioprospecting (i.e., biopiracy), the exploitation of a low-skilled labor force for science has been little examined from a human rights perspective. Reliance on cheap labor is not limited just to those directly involved in creating local biodiversity inventories but constitutes a whole set of other workers (cooks, porters, and logistical support staff), who contribute indirectly to the advancements of science and whose contribution is barely acknowledged, let alone financially remunerated. As precarious workers, it is difficult for laborers to use existing national and international labor laws to fight for recognition of their basic rights or easily to rely on biodiversity and environmental laws to negotiate recognition of their contribution to science. We explore to what extent the HRS can be used to encourage governments, civil society, and companies to provide basic labor and social rights to science. This should be of keen interest to geographers, who for the most part have limited engagement in human rights law, and has wider significance for those interested in exploitative labor and rights violations in the emerging bio- and green economy.